The Development of a Mobilising Communication Network: the Growth of Sąjūdis in Klaipeda in 1988 - Kraniauskas, Liutauras (Sociologija. Mintis ir veiksmas, 2011)
This article explores the structural conditions facilitating the rapid growth of public support for Sąjūdis (the Reform Movement of Lithuania) in Klaipeda in Autumn 1988. Here Sąjūdis is defined as a mobilising communication network; this concept opens the way for research into modes of information communication and for discussion of the issue of the efficiency of social networks. Methodologically, the study is based on the assumption that efficient communication of information within a social network involves reaching larger numbers of recipients, more effectively mobilises citizens for collective action, and increases the size and visibility of civic support. The growth of Sąjūdis is therefore treated as the development of a social communication network, where individualised channels of personal communication, which usually limit information-spread to the small-scale social networks of individuals, were transformed into more formalised modes and channels of communication. The argument is that the sudden growth of Sqjūdis support groups in Klaipeda should be treated not as a collective ideological awakening on a large scale, but rather as a cumulative effect of the formalisation of the movement. The formalisation of Sąjūdis expanded the social network beyond individualised channels of personal communication, solved legitimacy problems within the movement, opened channels for centralised information provision, and led to efficient management of mass support and collective actions. The article draws on materials published in both Sąjūdis and official media in 1988, on the internal records of the movement, and on interviews with former Sąjūdis leaders in Klaipeda.